AN ANALYSIS OF ERROR PHRASES ON INSTAGRAM’S CAPTION (A Study of Syntax) - Jauhar Helmie; siti iqlimah (Universitas Suryakancana, 2026)
This research paper analyze error phrases in Instagram captions, focusing on the syntactic structures used by public figures. With the rise of social media, particularly Instagram, the language employed in captions has become a significant aspect of communication, influencing followers and shaping linguistic norms. The study aims to identify common syntactic errors in captions written in English, especially by non-native speakers. Utilizing a qualitative descriptive method, data were collected from 30 Instagram captions of verified public figures with over 100,000 followers. The analysis revealed five types of phrases: noun phrases (NP), verb phrases (VP), adjective phrases (AdjP), adverb phrases (AdvP), and prepositional phrases (PP). The researcher found that there are eighteen noun phrase, verb phrase appeared in five, adjective phrase appeared in six, and prepositional phrase appeared in one. Among these, noun phrases were the most prevalent, highlighting the need for awareness regarding grammatical accuracy in social media communication. The findings suggest that public figures should be more cautious with their language use, as errors can mislead their audience and perpetuate incorrect language forms. This research contributes to the understanding of language use in digital contexts and offers recommendations for improving caption writing among social media users.Keywords: Syntax, Error phrase, Types of phrases, Instagram caption, Public figure.